2008
DOI: 10.1002/jcb.21975
|View full text |Cite
|
Sign up to set email alerts
|

EMMPRIN (basigin/CD147) expression is not correlated with MMP activity during adult mouse mammary gland development

Abstract: Extracellular matrix metalloproteinase inducer (EMMPRIN/basigin/CD147) is a cell surface protein, which has been associated with the induction of matrix metalloproteinase (MMP) genes during cancer metastasis. EMMPRIN plays a role in a variety of physiological processes as is evident by the diverse deficiencies detectable in EMMPRIN knockout mice. We have analysed the role of EMMPRIN in the induction of MMP genes during mammary gland differentiation and involution. Co-transfection studies showed that EMMPRIN ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Similarly, Szymanowska et al . reported that MMP‐3 and MMP‐12 were not correlated with EMMPRIN in mammary gland. EMMPRIN is not the only inducer of MMPs .…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, Szymanowska et al . reported that MMP‐3 and MMP‐12 were not correlated with EMMPRIN in mammary gland. EMMPRIN is not the only inducer of MMPs .…”
Section: Discussionmentioning
confidence: 96%
“…Western blots were done after semi-dry transfer of the proteins to a nitrocellulose membrane as described [25]. Mouse a-casein protein was detected using a rabbit-anti a-casein antiserum (Santa Cruz Biotechnology sc-98699) and a horse-radish-peroxidase linked goat anti-rabbit serum (Cell Signalling Technologies #7074).…”
Section: Observationmentioning
confidence: 99%
“…EMMPRIN may be engaged in distinct signaling pathways, directly promoting the invasive behavior of prostate cancer cells towards metastasis. This notion gains support from evidence indicating lack of correlation between EMMPRIN expression and MMP activity during adult mouse mammary gland development (30). Moreover, EMMPRIN has been shown to directly promote insoluble fibronectin assembly (21).…”
Section: Discussionmentioning
confidence: 67%